Jhum Cultivation Influence the Degradation of Hilly Environment (Journal of Environmental Science and Natural Resources, 2013)
This study was designed to identify the status of shifting (jhum) cultivation and its impact on environment in Rangamati district. A total 55 jhum cultivators were selected on the basis of purposive sampling technique from 5 upazillas of Rangamati district. Data were collected during the period October to December, 2009. The researcher collected information himself using direct and open questionnaire. The study revealed that most of the jhum cultivators were middle age (30-50 years), with illiterate (47.27%) and main occupation possessing jhum cultivation. The present status of agricultural land (hill/slope) of jhumia family in the studied area, about 60% of the respondents have only 1-2 acres of land for jhum cultivation and 25% of the respondents have 2.1-3 acres of land. The use of agro-chemical remains limited in the CHT. This is mainly because of financial constraints, lack of market access, and low requirement of chemical for traditional jhum cultivation. The maximum percentage of irrigation (74.55%) was mainly depended on rainfed in jhum cultivation. On the other hand about 45.55% respondents were responded that their income status were medium through shifting cultivation, 30.90% were responded high. Similarly in the study area it was found that a majority (45.45%) portion of respondents were responded that labour utilization in shifting cultivation was medium. This study also found that the environment was degraded gradually day by day. The maximum respondents (94.55%) had given opinion that deforestation was the major environmental problem created by shifting cultivation, 74.55% respondents had given opinion that shifting cultivation accelerated loss of top soil and 60.00% respondents had given opinion that lost of wild animals was occurring due to shifting cultivation. Biodiversity also degraded mostly. Excluding shifting cultivation there were many reasons of environmental degradation in the study area. Population growth is considered by 90% of the respondents as a major factor causing severe degradation of environment. Indiscriminate forest fire was responsible for environmental degradation. In addition cutting of hill, collection of soil, and extraction of stone, river erosion and land slide as responsible for degradation of environment. The study recommended that new methods must be developed, applied, and tested for sustainable management of jhum cultivation and environmental protection.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14840 J. Environ. Sci. & Natural Resources, 5(2): 339-344 2012